Glastonbury Abbey
The capitals of the arches and the continuous moldings which surround them, have a quality associated with Early English work. This partly is due to the use of the chisel, cutting deeply into the stone, but it is also the product of a Celtic use of molding, tying together each individual archway and linking the whole in an architectural way.